Treatment Efficacy and Compliance in Patients with Diabetic Macular Edema Treated with Ranibizumab in a Real-Life Setting - Giocanti-Auregan, Audrey; Delahaye-Mazza, Corinne; Quentel, Gabriel; Grenet, Typhaine; Nghiem-Buffet, Sylvia; Fajnkuchen, Franck; Best, Anne-Laurence; Cohen, Salomon Yves (Journal of ophthalmology, 2018)
Purpose. To assess real-life efficacy of ranibizumab and treatment compliance of patients with vision loss secondary to diabetic macular edema (DME). Methods. A retrospective study was conducted in DME patients treated with ranibizumab. Patients were monitored every 4 weeks for visual acuity (VA) and central retinal thickness (CRT) by SD-OCT. All patients received a loading dose of 3 monthly injections followed by retreatments on an as-needed basis. The primary endpoint was the change in VA at M12. Patient compliance to the follow-up and the correlation between the injection number and VA were also investigated. Compliance was compared to that of neovascular age-related macular degeneration (nAMD) patients. Results. Seventy-two eyes of 55 consecutive DME patients were included. At baseline, the mean VA was 56.5 letters and CRT was 470 μm. At M12, the mean VA was 63.4 letters (p<0.0001), 31.1% of patients had a VA > 70 letters, the mean VA change was +6.9 letters, and the mean CRT was 361.9 μm (p=0.0001) after a mean number of 5.33 intravitreal injections. In patients who received ≥7 injections, the VA gain and final VA were significantly higher than in patients who received <7 injections. At M12, 25.45% of DME patients were lost to follow-up versus 16.8% of nAMD patients (n=55). Discussion/Conclusion. Our study confirms the real-life efficacy of ranibizumab in DME at M12 and the need for a large number of injections to achieve better visual outcomes. We also showed a trend to a lower compliance in diabetic versus nAMD patients.